Circulating natural antibodies to inflammatory cytokines are potential biomarkers for atherosclerosis - Peng Wang; Huan Zhao; Zhenqi Wang; Xuan Zhang (BMC, 2018)
Abstract Background Inflammatory cytokines contribute to the development of atherosclerosis. Natural antibodies in the circulation have protective effects on common diseases including atherosclerosis-related conditions. Purpose The present study aimed to investigate the possible involvement of circulating IgG antibodies against inflammatory cytokines in atherosclerosis. Methods A total of 220 patients with diagnosis of atherosclerosis and 200 healthy controls were recruited. Seven linear peptide antigens were used to develop an enzyme-linked immunosorbent assay in-house for detection of plasma IgG antibodies against interleukin 1β (fragments IL1β-1 and IL1β-2), IL6, IL8, tumor necrosis factor alpha (fragments TNFα-1 and TNFα-2) and IL1α. Results Atherosclerotic patients had an increase in the levels of circulating IgG to TNFα-1(adjusted r2 = 0.038, p < 0.001) and IL1α (adjusted r2 = 0.025, p = 0.002) compared with control subjects. Female patients mainly contributed to increased anti-TNFα-1 IgG levels (adjusted r2 = 0.073, p < 0.001) and anti-IL1α IgG levels (adjusted r2 = 0.044, p = 0.003). In addition, female patients showed higher anti-IL1β-2 IgG levels than controls (adjusted r2 = 0.023, p = 0.026). There was no significant change of circulating IgG antibodies to other cytokines. ROC curve analysis showed an AUC of 0.564 for anti-TNFα-1 IgG assay with 22.8% sensitivity against a specificity of 90.0%, and an AUC of 0.539 for anti-IL1α IgG assay with 17.8% sensitivity against a specificity of 90.0%; the anti-IL1β-2 IgG assay had an AUC of 0.580 with 26.3% sensitivity against a specificity of 89.8% in female patients. There was no correlation between plasma IgG levels and carotid intima-media thickness. Conclusion Natural antibodies to inflammatory cytokines may be potential biomarkers for atherosclerosis.